Tourette-like behaviors in the normal population are associated with hyperactive/impulsive ADHD-like behaviors but do not relate to deficits in conditioned inhibition or response inhibition - Heym, Nadja; Kantini, Ebrahim; Checkley, Hannah L.R.; Cassaday, Helen J. (Frontiers, 2014)
Attention-Deficit Hyperactivity Disorder (ADHD) and Tourette Syndrome (TS) present as distinct conditions clinically; however, comorbidity and inhibitory control deficits have been proposed for both. Whilst such deficits have been studied widely within clinical populations, findings are mixed—partly due to comorbidity and/or medication effects—and studies have rarely distinguished between subtypes of the disorders. Studies in the general population are sparse. Using a continuity approach, the present study examined (i) the relationships between inattentive and hyperactive/impulsive aspects of ADHD and TS-like behaviors in the general population, and (ii) their unique associations with automatic and executive inhibitory control, as well as (iii) yawning (a proposed behavioural model of TS).One hundred and thirty-eight participants completed self-report measures for ADHD and TS-like behaviors as well as yawning, and a conditioned inhibition task to assess automatic inhibition. A sub-sample of fifty-four participants completed three executive inhibition tasks. An exploratory factor analysis of the TS behaviour checklist supported a distinction between phonic and motorlike pure TS behaviors. Whilst hyperactive/impulsive aspects of ADHD were associated with increased pure and compulsive TS-like behaviors, in attention in isolation was related to reduced obsessive-compulsive TS-like behaviors. TS-like behaviors were associated with yawning during situations of inactivity, and specifically motor TS was related to yawning during stress. Phonic TS and inattention aspects of ADHD were associated with yawning during concentration/activity. Whilst executive interference control deficits were linked to hyperactive/impulsive ADHD-like behaviors, this was not the case for inattentive ADHD or TS-like behaviors, which instead related to increased performance on some measures. No associations were observed for automatic conditioned inhibition.